Effectiveness Test of Epigallocatechin Gallate Cream Formula in Acne Vulgaris Therapy - Widyaningrum, Naniek; Dhea, Alda Rasni; Rofi, Alina Nur; Arief, Thendi Abdul; Timur, Willi Wahyu (Sciences of Pharmacy, 2026)
Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicles that affects more than 80% of adolescents and young adults. Conventional therapies such as antibiotics and topical retinoids have limitations in the form of resistance and irritation. Epigallocatechin gallate (EGCG) from green tea leaves (Camellia sinensis L.) has antibacterial, anti-inflammatory, and antioxidant activities that make it a safe natural anti-acne candidate. The aim of this study was to assess the clinical efficacy and safety of topical EGCG cream on the improvement of inflammatory and non-inflammatory acne lesions. A pre-post clinical trial was conducted on ten participants aged 17–50 years with active acne. Respondents applied 6% EGCG cream twice daily for six months. The number of lesions (papules, pustules, and blackheads) was evaluated monthly and analyzed using a paired t-test (p<0.05). There was a significant decrease in the number of papules (9.4 ± 5.97 to 3.0 ± 3.13), pustules (1.7 ± 1.57 to 0), and comedones (21.5 ± 10.76 to 4.2 ± 3.05) in five months (p<0.05), with the onset of improvement since the first month without side effects. Topical EGCG cream is effective and safe in reducing acne lesions quickly and sustainably. With its multi-target mechanism, EGCG has the potential to be developed as a phytocosmetic active ingredient for acne vulgaris therapy.